CONCEPTUAL METAPHOR IN MEDIA LANGUAGE - Sagatova Muborak Payzidinovna (Western European Studies, 2023)
this article discusses three large issues relating to media language. (1) How does conceptual metaphor theory affect the way one see the conceptual system that characterizes the main participants of communication in the media? (2) How do conceptual metaphors structure the language (and thought) used by the media? (3) Is the metaphorical mind of the participants of media communication a "self-contained" mind immune to the influence of context or is it affected by it?
Keywords: media discourse; conceptual metaphor; virtual reality